Status of Fisheries at Kg. Telok Melano and Kg. Telok Serabang - Roslianah, Asdari; Fazimah, Aziz; Harris Norman, Mustaffa Kamal (UNIMAS Publisher, 2024)
This study was conducted to assess the fishery status of villagers in Kg. Telok Melano dan Kg. Telok Serabang. The study was conducted using sets of questionnaires and interviews with fishermen from both villages. Questionnaires and interviews result have found that fishermen went to the sea mainly from March to October. They usually catch fish from waters around Sematan up to Tg. Datu. The most commonly used fishing gears are gill nets, drag nets, cast nets, hook and lines and scoop nets. The average total fish landing is 20 kg and it is usually for own consumption and distribution to nearby local markets. Some of the fish landings were also sent to wholesaler in Sematan. Since the opening of Pan Borneo expressway, fishermen were able to deliver their landings more efficiently. However, there are some issues faced by the fishermen, such as the high boat fuel price, competition with other fishing boats and maintenance problems especially for old boat and engines. Due to these problems, fishermen have started to involve in other income opportunities such as homestay services and small food businesses.